Methods of treating gestational diabetes through an adapted diet and physical activity - Skorek, Klaudia; Babiak, Rafał; Bajak, Karolina; Czuchryta, Paulina; Domańska, Anastazja; Gawęda, Agnieszka; Grabek, Agata; Rutkowska, Julia; Rzęsa-Tokarczyk, Żaneta; Urbańczyk, Agnieszka (Journal of Education, Health and Sport, 2023)
Gestational diabetes mellitus (GDM) is a carbohydrate tolerance disorder that results in elevated blood glucose levels and was first recognized during pregnancy. Diabetes is the most common metabolic complication that complicates pregnancy. Therefore, it is important to quickly diagnose and prevent the effects of diabetes, which may arise in the mother and fetus. The occurrence of diabetes during pregnancy is a risk factor for diabetes and cardiovascular diseases later in life. Studies have shown a reduction in complications in patients with gestational diabetes after personalized health education in the field of nutrition. All pregnant women should be screened for impaired glucose tolerance as soon as possible after pregnancy is diagnosed. In the risk group, additionally, a 75g OGTT test should be performed on the first visit. Gestational diabetes affects one in ten pregnant women worldwide, and this percentage is increasing day by day. The main goal is to strive, during therapy, to equalize the glycemic value. The aim of this publication is to present the diagnostic process and, most importantly, the treatment of diabetes diagnosed in pregnancy. The publication focuses on gestational diabetes treated with an adapted diet, exercise and lifestyle changes. This publication describes how to create a balanced diet with a low glycemic index and how to choose physical exercise for a patient with gestational diabetes.